Social Media Perceptions and Internet Verification Skills Associated With Human Papillomavirus Vaccine Decision-Making Among Parents of Children and Adolescents: Cross-sectional Survey - Erika L Thompson; Sharice M Preston; Jenny K R Francis; Serena A Rodriguez; Sandi L Pruitt; James-Michael Blackwell; Jasmin A Tiro (JMIR Publications, 2022)
BackgroundHuman Papillomavirus (HPV) vaccination is recommended for children aged 11-12 years in the United States. One factor that may contribute to low national HPV vaccine uptake is parental exposure to misinformation on social media. ObjectiveThis study aimed to examine the association between parents' perceptions of the HPV vaccine information on social media and internet verification strategies used with the HPV vaccine decision-making stage for their child. MethodsParents of children and adolescents aged 9-17 years were recruited for a cross-sectional survey in North Texas (n=1192) and classified into 3 groups: children and adolescents who (1) were vaccinated, (2) unvaccinated and did not want the vaccine, and (3) unvaccinated and wanted the vaccine. Multinomial logistic regression models were estimated to identify factors associated with the HPV vaccine decision-making stage with children and adolescents who were vaccinated as the referent group. ResultsOf the 1192 respondents, 44.7% (n=533) had an HPV-vaccinated child, 38.8% (n=463) had an unvaccinated child and did not want the vaccine, and 16.4% (n=196) had an unvaccinated child and wanted the vaccine. Respondents were less likely to be "undecided/not wanting the vaccine" if they agreed that HPV information on social media is credible (adjusted odds ratio [aOR] 0.40, 95% CI 0.26-0.60; P=.001), disagreed that social media makes them question the HPV vaccine (aOR 0.22, 95% CI 0.15-0.33; P<.001), or had a higher internet verification score (aOR 0.74, 95% CI 0.62-0.88; P<.001). ConclusionsInterventions that promote web-based health literacy skills are needed so parents can protect their families from misinformation and make informed health care decisions.